2019
DOI: 10.1002/jpen.1601
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Administration of Mother's Milk Prior to Gavage Feeding in Preterm Infants: A Pilot Randomized Control Trial

Abstract: Background: Oropharyngeal administration of mother's colostrum in early days has an immunoprotective effect in preterm infants. Objectives: Our aim was to study the effect of oropharyngeal administration of mother's milk (OPAMM) on decreasing the incidence of nosocomial sepsis. Methods: In a pilot prospective randomized study on preterm (<32 weeks gestation and 1500 g weight) infants, we compared OPAMM practice (applying 0.2 mL of mother's colostrum or milk prior to gavage feeding until full oral feeding is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(150 citation statements)
references
References 31 publications
(45 reference statements)
7
137
1
5
Order By: Relevance
“…Methodological weaknesses existed for most of the included studies. Six studies [17,18,22,23,33,34] had a low ROB in random sequence generation, with one study [35] reported a high risk and two [36,37] reported an unclear risk. Allocation concealment was of high risk in one study [35] and of unclear risk in three studies [17,18,37].…”
Section: Rob Of Rctmentioning
confidence: 99%
See 4 more Smart Citations
“…Methodological weaknesses existed for most of the included studies. Six studies [17,18,22,23,33,34] had a low ROB in random sequence generation, with one study [35] reported a high risk and two [36,37] reported an unclear risk. Allocation concealment was of high risk in one study [35] and of unclear risk in three studies [17,18,37].…”
Section: Rob Of Rctmentioning
confidence: 99%
“…After eliminating the studies of Zhang et al [23], Glass et al [18], and Romano-Keeler et al [35] for the all-cause mortality rate, six studies [17,22,33,34,36,37], with a total sample of 505 preterm infants were included to measure the mortality rate (Fig. 3c).…”
Section: Effect On the All-cause Mortality Ratementioning
confidence: 99%
See 3 more Smart Citations